Involvement of the chloroplast gene ferredoxin 1 in multiple responses of Nicotiana benthamiana to Potato virus X infection - Yang, Xue (J Exp Bot, 2020)
The chloroplast protein ferredoxin 1 (FD1), with roles in the chloroplast electron transport chain, is known to interact with the coat proteins (CPs) of Tomato mosaic virus and Cucumber mosaic virus. However, our understanding of the roles of FD1 in virus infection remains limited. Here, we report that the Potato virus X (PVX) p25 protein interacts with FD1, whose mRNA and protein levels are reduced by PVX infection or by transient expression of p25. Silencing of FD1 by Tobacco rattle virus-based virus-induced gene silencing (VIGS) promoted the local and systemic infection of plants by PVX. Use of a drop-and-see (DANS) assay and callose staining revealed that the permeability of plasmodesmata (PDs) was increased in FD1-silenced plants together with a consistently reduced level of PD callose deposition. After FD1 silencing, quantitative reverse transcription–real-time PCR (qRT–PCR) analysis and LC-MS revealed these plants to have a low accumulation of the phytohormones abscisic acid (ABA) and salicylic acid (SA), which contributed to the decreased callose deposition at PDs. Overexpression of FD1 in transgenic plants manifested resistance to PVX infection, but the contents of ABA and SA, and the PD callose deposition were not increased in transgenic plants. Overexpression of FD1 interfered with the RNA silencing suppressor function of p25. These results demonstrate that interfering with FD1 function causes abnormal plant hormone-mediated antiviral processes and thus enhances PVX infection.